Honing, Loving, and Nurturing: A Study of Mothers’ Role in Family (Martabat: Jurnal Perempuan dan Anak, 2020)
Parents, both mother and fathers have significant roles in a family, starting from nurturing the chores, until caring for and educating children. Although those roles are parents’ responsibility, however, practically, mothers have dominant action in educating the children. Mothers do not only nurture their children, they also hone the children’s characters, and educate them lovely. Some matters which then raise are, not all mothers take those three roles at once. Their role as educator at home, frequently is not done properly due to some factors. That case then obstructs the children’s growth and development. The current study aims to explain the important role of mothers in household, beginning from honing, loving and and nurturing children. Furthermore, the recent study also makes a serious effort in finding the inhibitor factors of mothers’ role as an educator, which then is expected to be parents’ knowledge to prepare themselves as educators in their family. This research applies qualitative approach, by design content analysis where the documents are taken from accredited and relevant articles of reputable journal. The data collection method is documentation which then reported descriptively. The result of this research shows that the mothers’ presence in honing, loving and nurturing children is very crucial because it influences through children’s character building. Besides, there are three factors which are needed to fulfill by mothers to play their role properly in a family, they are phisically factor, mentality, and knowledge.